The Realized Benefits from Bioprospecting in the Wake of the Convention on Biological Diversity - James S. Miller (Washington University Journal of Law & Policy, 2015)
The emergence of methods to miniaturize in-vitro bioassays in the 1980s allowed for rapid evaluation of large numbers of plant samples with newfound efficiency. Contemporaneously, the United Nations Conference on Environment and Development (Earth Summit) fundamentally changed the legal status of ownership for biological resources, legally mandating that benefits derived from natural sources be shared in an equitable manner with the country where the species was first collected. It was expected from this reform that significant royalty payments would be paid to countries in which the species originated. However, this expectation did not hold true as few marketable discoveries were made. Despite this initial disappointment, a number of non-monetary benefits materialized, including a contribution to general knowledge, building research, development, conservation capacity, improved quality of life for rural communities, and changes in the ethical practices of international collaboration. These, as well as other advancements, will contribute to a more equitable scientific collaboration in the future.
Keywords: environment; earth summit; bioassays; biological resources; United Nations Conference on Environment and Development